1980
DOI: 10.1128/jb.141.2.502-507.1980
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle-specific inhibition by chloramphenicol of septum fromation and cell division in synchronized cells of Bacillus subtilis

Abstract: The relationship between protein synthesis and processes of cell division was studied by using synchronized cells of Bacillus subtilis 168. The addition of chloramphenicol at the beginning of synchronous growth prevented septum formation and cell division, suggesting the requirement of protein synthesis for the processes of cell division. Experiments in which the drug was added to the cells at different cell ages showed that the protein synthesis required for the initiation of septum formation was completed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…The most characteristic morphological change induced by kendomycin treatment was the formation of irregular septa, suggesting that kendomyci ninhibits the cell septation system and induces the formation of fibrillar wall materials. Similar (but not identical) staphylococcal cell wall structures caused by the treatment of cells with various antibiotics, such as chloramphenicol [ 40 ], oritavancin [ 41 ] and penicillin, have been previously reported [ 42 44 ].…”
Section: Resultssupporting
confidence: 63%
“…The most characteristic morphological change induced by kendomycin treatment was the formation of irregular septa, suggesting that kendomyci ninhibits the cell septation system and induces the formation of fibrillar wall materials. Similar (but not identical) staphylococcal cell wall structures caused by the treatment of cells with various antibiotics, such as chloramphenicol [ 40 ], oritavancin [ 41 ] and penicillin, have been previously reported [ 42 44 ].…”
Section: Resultssupporting
confidence: 63%
“…3) by acting externally on the cell membrane or cell wall, or these phenomena may reflect an indirect, internal effect of low external pH. Specific protein synthesis events appear to be necessary for septation in Bacillus subtilis (20) and also for cell division in B. subtilis (20), Escherichia coli (5,33), and Synechococcus AN (19). Hence, exposure to a low pH might alter the intracellular environment and cause the synthesis of defective septationand division-specific proteins, or such exposure might alter the activities of these proteins.…”
Section: C2-(na-morph)amentioning
confidence: 99%
“…Division processes in Bacillus subtilis are intimately connected with the other cell cyclespecific events, such as chromosome replication, surface extension, or age-dependent synthesis of some cellular components (for reviews, see references 7,10,22,35). In our previous report, the age dependency of the effects of chloramphenicol on both septum formation and cell division in B. subtilis was shown (27). Applying the concept of the transition point of protein synthesis (24,40,41) (transition point is a point in the cell cycle before which an agent will delay or prevent the forthcoming cell cycle event and after which it will not) to the cell cycle of this bacterium, we demonstrated that there are two chloramphenicol transition points in the cycle; one, CAP TP(Sept), is for septum formation and occurs at age 0.23, and the other, CAP TP (Div), is for cell division and occurs at age 0.64.…”
mentioning
confidence: 98%